The use of mobile electronic devices and their impact on the increase of affections in university students - Hidalgo Cajo, Byron Geovanny; Mayacela Alulema, Íngel; Hidalgo Cajo, Diego Patricio; Hidalgo Cajo, Iván Mesías (SATHIRI, 2019)
Posture is the ability to keep the center of gravity on a support base and is determined by factors such as personality, mental attitude, occupation, genetics, clothing, age, health status and sociocultural models; however there are factors that develop postural changes such as prolonged use of mobile electronic devices. Research identifies the various activities of students with mobile devices in turn conveys the conditions that they cause health by overuse, research was conducted with a sample (n = 368) students University National of Chimborazo (UNACH) study was a prospective, non experimental, transversal, descriptive and quantitative association. Subsequently the results obtained that 70% of students use smartphones, 23% tablets and 7% laptops, the main activities carried out are communicating with family and friends 45%, for entertainment 25%, activities we analyzed academic 23%, connect to the Internet 4% and search information 3%, once known the influence of excessive use of mobile devices light is given to the main conditions they produce being the most regular muscle inbalances with 47 % followed by stooping in 28%, 11% cervical problems, Whatsappitis 8% and other conditions such as Nomofobia, phubbing, and ocular tension Vibranxiety 7%,It concludes that excessive use of these devices seriously affect the appearance of various conditions that affect the university student health.